Intrinsic Detectivity Limits of Organic Near‐Infrared Photodetectors. Issue 47 (19th October 2020) - Gielen, Sam; Kaiser, Christina; Verstraeten, Frederik; Kublitski, Jonas; Benduhn, Johannes; Spoltore, Donato; Verstappen, Pieter; Maes, Wouter; Meredith, Paul; Armin, Ardalan; Vandewal, Koen
Abstract: Organic photodetectors (OPDs) with a performance comparable to that of conventional inorganic ones have recently been demonstrated for the visible regime. However, near‐infrared photodetection has proven to be challenging and, to date, the true potential of organic semiconductors in this spectral range (800–2500 nm) remains largely unexplored. In this work, it is shown that the main factor limiting the specific detectivity ( D *) is non‐radiative recombination, which is also known to be the main contributor to open‐circuit voltage losses. The relation between open‐circuit voltage, dark current, and noise current is demonstrated using four bulk‐heterojunction devices based on narrow‐gap donor polymers. Their maximum achievable D * is calculated alongside a large set of devices to demonstrate an intrinsic upper limit of D * as a function of the optical gap. It is concluded that OPDs have the potential to be a useful technology up to 2000 nm, given that high external quantum efficiencies can be maintained at these low photon energies. Abstract : The specific detectivity of near‐infrared organic photodetectors is found to be limited by non‐radiative recombination, which is also known to be the main contributor to open‐circuit voltage losses. Investigation of the relation between open‐circuit voltage, dark current, and noise current allows the calculation of an intrinsic upper limit of D * as a function of the optical gap.